Pollen storages in nests of bees of the genera Partamona, Scaura and Trigona (Hymenoptera, Apidae) - Rech, André Rodrigo; Absy, Maria Lúcia (Revista Brasileira de Entomologia, 2011)
Bees and angiosperms established a mutualistic relationship along the evolutionary time. The aim of this study is to contribute for the understanding of this relation analyzing pollen stored by stingless bees colonies distributed along the Rio Negro. Fourteen species of Meliponini from the genera Partamona, Scaura, and Trigona were studied with regard to the content of pollen pots. The pollen material was removed from the pollen pots, homogenized, and prepared according to the usual acetolysis technique. The overlap of the trophic niche and the grouping of species by similarity of niches was calculated. The identification revealed 78 pollen types belonging to 36 families, being 37 types attractive and 16 considered as promoters of a temporary specialization event. With the results, it was possible to indicate a list of important plants for meliponiculture in the Amazon.